2011
DOI: 10.1038/ejhg.2011.84
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic heterogeneity in British patients with a founder mutation in the FHL1 gene

Abstract: Mutations in the four-and-a-half LIM domain 1 (FHL1) gene, which encodes a 280-amino-acid protein containing four LIM domains and a single zinc-finger domain in the N-terminal region, have been associated with a broad clinical spectrum of X-linked muscle diseases encompassing a variety of different phenotypes. Patients might present with a scapuloperoneal myopathy, a myopathy with postural muscle atrophy and generalized hypertrophy, an Emery-Dreifuss muscular dystrophy, or an early onset myopathy with reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We found a prominent involvement of the paraspinal muscles at the early stage and preservation of the triceps brachii and intrinsic hand muscles at the progressed stage. Two recent studies reported cases with mutations in the second LIM domain that showed a relatively marked involvement of the biceps brachii muscles [9,11]. Our imaging results also confirmed these clinical observations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found a prominent involvement of the paraspinal muscles at the early stage and preservation of the triceps brachii and intrinsic hand muscles at the progressed stage. Two recent studies reported cases with mutations in the second LIM domain that showed a relatively marked involvement of the biceps brachii muscles [9,11]. Our imaging results also confirmed these clinical observations.…”
Section: Discussionsupporting
confidence: 89%
“…Subsequent reports identified other mutations in FHL1, such as those associated with reducing body myopathy (RBM), rigid spine syndrome, Emery-Dreifuss muscular dystrophy (EDMD), EDMD-like joint contracture and cardiomyopathy, and pathological diagnosed myofibrillar myopathy [4][5][6][7][8][9]. Nearly 30 mutations in the FHL1 myopathies have been reported [9,10], with variations in the age of onset, muscle involvement, and severity even within the same mutation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations causing this phenotype are distributed across the FHL1 gene. The latest report of a novel founder mutation in FHL1 described a heterogeneous spectrum of phenotypes caused by a 3‐bp insertion mutation (p.Phe127Thr128insIle) 23. Onset of disease was mostly in adulthood with proximal lower limb weakness and cervical rigidity but no heart involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkable inter‐ and intrafamilial variability of phenotypes has been noted, ranging from early, severe presentations in childhood to slow progressive onset in adulthood. However, most affected individuals develop symptoms in the second decade of life .…”
Section: Emery–dreifuss Muscular Dystrophymentioning
confidence: 99%